PARENTAL RIGHTS TO PARTICIPATE IN A CHILD’S PERSONALITY DEVELOPMENT AND ITS RELIGIOUS AND MORAL UPBRINGING AND THE CHILD’S RIGHT TO FREEDOM OF CHOICE: OBSERVATIONS ON THE FIELD OF TENSION CAUSED BY THE IRRATIONAL IN A HUMAN RIGHTS DISPENSATION - JMT Labuschagne; JC Bekker; GJ van Zyl (Obiter, 2023)
One of the factors that must be taken into account in child custody cases is the religious upbringing of the child. If the parents agree, there is normally no issue. The courts will not interfere, unless the parents’ religious practices are not in the child’s best interests. Courts have consistently held that the parents’ autonomy in this regard is a fundamental right. In this article the authors argue that religious upbringing is implicit in parenthood. At an early age a child does not have a choice. It is indeed strange to suggest that young children have a choice, as if it is presented to them on a menu. Parents have a right and a duty to promote the development of their children’s character, value system and spiritual and moral well-being.